Manufacture of Water Pipe From Clampshell Powder Materials - Abdul Rahmansyah; zulfikar zulfikar; bobby umroh (Universitas Medan Area, 2018)
In general, household waste water pipelines use plastic pipes of PVC type that are not environmentally friendly and are relatively expensive. Therefore, this research will design molds and manufacture of composite pipes using raw materials of clampshell powder. The raw material used is clampshell powder with the composition of MgO and CaO compounds which is about 22.28% and 66.70%. The mixture of materials used consisted of clampshell powder with a size of 40 mesh, catalyst, and unsaturated polyester resin as a matrix. The objective of this study is manufacture of water pipes made from polymer composites reinforced by clampshell powder. Composite pipe manufacturing is carried out using the casting method. Pipe molds are made of stainless steel with a diameter of 40.46 mm (1.6 in) and an outer diameter of 50.8 mm (2 in). This mold size follows SNI 06-0084-2002 standards. The results of the study, water pipes from polymer composite material reinforced by clampshell powder with an inner diameter size of 40.64 mm and varying outside diameter. This variation depends on the composition of the clampshell powder in composite materials. The greater the clampshell powder composition, the more easily the maximum pipe wall thickness can be obtained. The average wall thickness variation is 3.35 mm. This variation is still included in the polymer water pipe requirements, which is a minimum of 2 mm.